PERFECTION FROM INCEPTION: STANDARDS FOR BIOCHEMISTRY UNDERGRADUATE CERTIFICATE PRACTICAL - KAUR, JASPREET; SAMADHIYA, AMIT; SINGH, MITHILESH KUMAR; CHANE, RENU; GUPTA, GITANJALI; KAUR, JASWANT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The undergraduate biochemistry practical’s are the routine test performed in all the medical laboratories. Few of these have been certified practical by competency-based medical education. This will help the teachers access the depth of theoretical and practical knowledge as well as judge their communication skills. To detect the basic concept of quality control in the biochemistry laboratory. Methods: Quantitative analysis was conducted with a purposive sample, at the Noida International institute of medical sciences by the department of biochemistry. 150 students performed the practical on serum albumin in two batches after the demonstration by the faculty. The results were collected through Google forms. The mean, SD, coefficient of variation, and bias were calculated. Results: Both batches showed significant improvement in repeating the practical. Batch a performance was markedly improved after disclosing the optical density of the standard. Conclusion: Teaching basic quality standards used in the biochemistry laboratory and emphasizing the preanalytical errors made during the 1st year of practical’s, markedly improved the performance.